Unified Synthesis of (–)-Folicanthine and (–)-Ditryptophenaline Enabled by a Room Temperature Nickel-Mediated Reductive Dimerization - Luo, Long; Zhang, Jian-Jian; Ling, Wei-Jian; Shao, Yong-Liang; Wang, Ya-Wen; Peng, Yu (Synthesis, 2014)
A Ni·Phen-mediated reductive homocoupling of an optically active tertiary bromide has been efficiently achieved after the systematic screen of reaction conditions including ligands. This key step establishes sterically hindered vicinal quaternary stereocenters embedded in natural bispyrrolo[2,3-b]indoline alkaloids, thus enabling to realize the first asymmetric total synthesis of (–)-folicanthine via the detailed investigation of a challenging double decarboxylation. Notably, the concise synthesis of diketopiperazine alkaloid (–)-ditryptophenaline was also completed from the common dimeric intermediate.
Keywords: nickel catalysis; reductive homocoupling; dimeric alkaloids; total synthesis; vicinal quaternary stereocenters